Comparison of preferences for end-of-life care among patients with advanced cancer and their caregivers: A discrete choice experiment. (October 2015) - Malhotra, Chetna; Farooqui, Muhammad Assad; Kanesvaran, Ravindran; Bilger, Marcel; Finkelstein, Eric
Background: Patients with advanced cancer often have to make difficult decisions, such as how much to spend on moderately life-extending treatments. This and other end-of-life decisions are also influenced by their informal caregivers. Understanding the relative value that patients and their caregivers place on various aspects of end-of-life care can help clinicians tailor treatments to best meet the preferences of their patients. Aim: To quantify willingness to pay of patients with advanced cancer and their caregivers to extend the patients' life by 1 year and to compare this result to their willingness to pay for other end-of-life improvements. Design: Cross-sectional survey using a discrete choice experiment. Participants: A total of 211 patients with stage IV cancer and their informal caregivers. Results: The willingness to pay of patients to extend their life by 1 year (S$18, 570; 95% confidence interval: S$6687–S$30, 542) was not statistically different from their willingness to pay to avoid severe pain (S$22, 199; S$11, 648–S$32, 450), to die at home (S$31, 256; S$21, 249–S$41, 391), not be a burden on family and friends (S$4051; −S$3543 to S$11, 568), or to receive a high-quality health-care experience (S$16, 191; S$9266–S$23, 037). Consistent with our hypothesis, caregivers had a greater willingness to pay than patients to extend life (S$61, 368; S$37, 030–S$86, 210) and for most other end-of-life improvements. Conclusion: Results highlight the importance of pain management, supporting home deaths, and addressing other end-of-life concerns, in addition to efforts to extend life. Differences in willingness to pay of patients and caregivers suggest the need for eliciting patient preferences during treatment decision making as opposed to relying on caregiver input.